Microgrid Application of Four-Leg Three-phase Inverter - da Silva, José Francisco Resende; Miranda, Fábio Ferreira, Hugo; Mello, Eder; Rodrigues, Marcos; Pereira, Thobias; Nielson, Rafael (International Journal of Advanced Engineering Research and Science, 2020)
The On-grid inverters use energy from DC sources to feed AC consumers, and also the main grid whenever there is a surplus of energy, as distributed energy resources. A caveat of on-grid inverters generally implied by worldwide electrical standards imposes that whenever a fault occurs on the main grid, local generation must be shut off to prevent unintentional islanding. However, there are some applications where distributed resource systems could improve reliability, and on-grid inverters with off-grid function can continue to operate even when grid power outages occur, known as intentional islanding. Today’s micro-grids have better sensing capabilities and superior semiconductor technologies that allow faster response times and higher maximum ratings, improving micro-grid equipment isolation and control capabilities. In this paper, we review anti-islanding tests performed on on-grid inverters with off-grid function in Brazil for conformity assessments and present a case study of a 20 kW hybrid inverter.